TMOD-27. EFFICACY OF SOLUBLE PANOBINOSTAT (MTX110) IN PRECLINICAL MODELS OF ADULT GLIOBLASTOMA. (9th November 2020) - Ashley, David; Keir, Stephen T; Roskoski, Martin A; Davies, Rhian; Williams, Ben; Damment, Stephen J P; Conlon, Kelly
Abstract: INTRODUCTION: Panobinostat is a histone deacetylase (HDAC) inhibitor with antineoplastic and anti-angiogenic effects in glioma. HDAC inhibitors have demonstrated therapeutic efficacy preclinically via multiple mechanisms, including the induction of cell-cycle arrest, differentiation, senescence, apoptosis, mitotic cell death, autophagy, generation of reactive oxygen species, inhibition of angiogenesis and metastasis, and improvement in tumor immunity. One of the biggest challenges in treating glioblastoma is achieving effective local drug concentrations, and trials using systemic administration of therapeutics have failed in GBM despite compelling pre clinical evidence. MTX110 (Midatech Pharma plc) is a water-soluble form of panobinostat currently in clinical development for DIPG and medulloblastoma using direct tumour delivery. We explored the therapeutic potential of MTX110 in GBM in our preclinical in vivo adult brain tumor models. METHODS: Tumor-bearing mice were stratified to either the vehicle control or treatment group based on median tumor volume and were treated with Panobinostat/MTX110 at a dose of 15mg/kg IP, twice weekly for 5 consecutive weeks. The response to treatment was assessed by delay in tumor growth in days, expressed as a T (Treated) - C (Control) value. Statistical analysis was performed using SAS (a statistical analysis program) and the Wilcoxon rank order test. RESULTS: MTX110 produced non-significant growth delays of 10.76 and 2.01 days (p Value ≥ 0.072 NS) in IDH wild type xenograft lines. However, in an IDH1 mutated line, MTX110 produced a significant growth delay of 23.35 days (p Value ≤ 0.018). Further work is ongoing to look at the therapeutic potential of MTX110 in combination with radiation in both IDH wild type and IDH mutated xenograft lines.